REDUCTION OF GOETHITIC IRON ORE USING THERMOGRAVIMETRIC METHOD - Adji Kawigraha; Sri Harjanto; Johny W. Soedarsono; Pramusanto Pramusanto (Indonesian Mining Journal, 2013)
Compared to main iron ore minerals, either hematite or magnetite, Indonesian goethite is relatively abundant. However, this is not common to be used as feed material in iron making industries. Limitation in Indonesian high quality iron ore resources, the iron making industries have to seek another iron source such as the low grade iron ore of goethitic ore. Evaluation using thermogravimetric method was employed for analyzing behavior of goethitic composite pellet during reduction. The data show that reduction of goethitic iron ore is started by transforming goethite to hematite and then followed by iron reduction. The reduction was started by Fe3O4 formation at 442 °C and Fe at 910 °C. At those temperatures the composite pellet lost its weight. Identifying the FeO is hardly difficult due to the short range of phase existence.